Vibriosis in aquaculture - Romi Novriadi (Journal Omni-Akuatika, 2016)
Current growth in aquaculture production is parallel with the increasing number of diseases outbreaks and can affect the production, profitability and sustainability of the industry worldwide. Among the groups of pathogenic microorganisms, vibriosis is the well-known cause of severe economic losses and responsible for (massive) mortality of cultured shrimp, fish and shellfish. Antibiotics and chemicals have been applied in farms for traditional treatment and prevention of Vibriosis. However, the frequent use of chemotherapeutic agents has allowed for the development of drug-resistant strainsand has led to allergy and toxicity in humans. Therefore, the use of prophylactic approaches to stimulate and enhance the immune responses becomes urgent. In this short review, the application of immunostimulant, vaccine, probiotics and quorum quenching molecules to inhibit the communication of Vibrio spp were presented. Key words: Vibriosis, Aquaculture, Antibiotics, Prophylactic, Virulence, Immune response